RITUAL AKKATTERE SEBAGAI KEPERCAYAAN MASYARAKAT DI DESA TANA TOWA KECAMATAN KAJANG KABUPATEN BULUKUMBA - Nurilmi, Nurilmi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study discusses the Akkattere ritual as a community belief in Tana Towa Village, Kajang District, Bulukumba Regency. The method used is a qualitative method. Data collection techniques used are Observation, Interview, and Dokumentation. In analyzin a data can be done by means pf data reduktion, data presentation, and drawing conclusions. It can be concluded that Akkattere is an activity in the form of a traditional party which includes hair cutting carried out by traditional stakeholders of the Tana Towa area. This ritual is a pair/message from their ancestors which is still being carried out. With the aim ofgetting a happiness in this worl and the here after. The implementation process also requires a very large cost. Akkattere also has no value if those who carry it out do dot have good behavior,